2009
DOI: 10.1111/j.1440-1754.2009.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of portable continuous wave Doppler ultrasound (ultrasonic cardiac output monitor) for cardiac output measurements in neonates

Abstract: Background and study purpose: The ultrasonic cardiac output monitoring (USCOM, USCOM Pty Ltd, Coffs Harbour, NSW, Australia) device provides a new method of non-invasively assessing cardiac output (CO). It has been successfully used in adults, but there have been few studies in neonates. Aims: To study the inter-operator reliability, and to compare the aortic (systemic) CO and pulmonary CO in a neonatal population. Patient and methods:In a study using the USCOM device, we have determined: (i) the inter-operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Of note, a difference in LVO and RVO was also seen when assessed by conventional echocardiography. This is in line with the results of our study using the USCOM technique in neonates (LVO: 228.3 (95% CI 202.1 to 254.5) ml/kg/min) vs RVO 282.3 (95% CI 256.0 to 308.5) ml/kg/min; p =0.006) 2. Of interest, this imbalance was not substantially modulated by the presence of a persistent ductus arteriosus in our cohort.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Of note, a difference in LVO and RVO was also seen when assessed by conventional echocardiography. This is in line with the results of our study using the USCOM technique in neonates (LVO: 228.3 (95% CI 202.1 to 254.5) ml/kg/min) vs RVO 282.3 (95% CI 256.0 to 308.5) ml/kg/min; p =0.006) 2. Of interest, this imbalance was not substantially modulated by the presence of a persistent ductus arteriosus in our cohort.…”
supporting
confidence: 91%
“…There may also be a systemic error in the calculation of the cross-sectional area of aortic and pulmonary values (from the Nidorf equations4), and as the weight of the baby increases, the error increases as well, as demonstrated in our study 2. The Nidorf equations for these neonates are also based on a small number of measurements, and this is also a limitation of the method.…”
mentioning
confidence: 64%
“…The USCOM is a relatively new continuous-wave Doppler (CWD) device for measuring hemodynamics noninvasively at the bedside, which appears to be both accurate and reproducible [20][21][22][23][24]. The USCOM calculates DO 2 from the standard formula (see Subjects and methods), and the Smith-Madigan method calculates the SmithMadigan inotropy (SMI) value and inotropy index (SMII) [25].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that echo-based measures and USCOM measures were not interchangeable. As in the term infants, the USCOM-measured RV output was signifi cantly greater than the LV output in a group of preterm infants suggesting the device systematically overestimates RV output [ 17 ]. In a subsequent publication, Meyer et al suggested that the USCOM device undergo further controlled clinical trials before its wide application in the neonatal ICU [ 18 ].…”
Section: The Cardiovascular Systemmentioning
confidence: 97%